(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Febrile seizures are the most common type of seizures in children. It is prevalent in children aged between 6 months and 60 months, with an incidence of 2-5%. On the other hand, iron deficiency anemia is the most common hematologic disease of infancy and childhood with a period of incidence that coincides with the time of developing febrile seizures. Therefore, it is hypothesized that there is a possible association between this two conditions. The relationship between iron deficiency anemia and febrile seizures had been examined in several studies with conflicting results. This study was designed to elucidate this association. The purpose of this study was to determine the association between Iron deficiency anemia and febrile seizures in children. Materials and methods: In this case-control study 80 children with a diagnosis of febrile seizures, aged between 6 months and 60 months who were visited Pediatric ward and Pediatric outpatient department of Chattogram Medical College Hospital, Chattogram, during June 2012 to may 2013 were enrolled as cases. The control group consisted of 80 febrile children without seizure and were matched to the cases by gender and age. Iron deficiency anemia was diagnosed by hematologic investigations of hemoglobin value <11g%, serum ferritin value <30ng/mL and RDW > 15%. Results: A total 36 out of 80(45%) seizure cases had iron deficiency anemia whereas, 08 out of 80(10%) controls were found to have iron deficiency anemia. There was statistical significance of difference observed in two groups (p<0.001). Univariate risk factor analysis for control versus case showed odds ratio 7.364 (3.138 – 17.279) (95 % CI). The mean serum ferritin level of cases and controls were 43.01±29.77 and 72.36±38.66 (ng/mL) respectively (p<0.001). The mean value of HB%, MCV, MCH, and RDW% were also found significantly lower in the cases than controls (p<0.001). Conclusion: Iron deficiency anemia was more frequent among children with febrile seizures than those with febrile illness alone. The findings of this study suggest a positive association between iron deficiency and febrile seizures in children and screening for Iron deficiency anemia should be considered in children presenting with febrile seizures. JCMCTA 2018 ; 29 (2) : 9-15